Encapsulated Cobalt–Porphyrin as a Catalyst for Size‐Selective Radical‐type Cyclopropanation Reactions. Issue 17 (24th March 2014) - Otte, Matthias; Kuijpers, Petrus F.; Troeppner, Oliver; Ivanović‐Burmazović, Ivana; Reek, Joost N. H.; de Bruin, Bas
Abstract A cobalt–porphyrin catalyst encapsulated in a cubic M8L6 cage allows cyclopropanation reactions in aqueous media. The caged‐catalyst shows enhanced activities in acetone/water as compared to pure acetone. Interestingly, the M8L6 encapsulated catalyst reveals size‐selectivity. Smaller substrates more easily penetrate through the pores of the "molecular ship‐in‐a‐bottle catalysts" and are hence converted faster than bigger substrates. In addition, N‐tosylhydrazone sodium salts are easy to handle reagents for cyclopropanation reactions under these conditions.